Pengaruh Kepemimpinan Kepala Sekolah dan Iklim Sekolah Terhadap Kesiapan Guru dalam Penerapan Kurikulum Merdeka di SD Se-Kecamatan Sumpur Kudus: Penelitian - Heliwasnimar; Elda Herlina; Muhammad Fazis (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine and analyze the influence of principal leadership on teacher readiness, determine and analyze the influence of school climate on teacher readiness, determine and analyze the influence of principal leadership and school climate on teacher readiness in elementary schools throughout Sumpur Kudus District. This study uses a causal correlation study. The population in this study were 256 elementary school teachers in Sumpur Kudus District. The research sample numbered 72 people. The research instruments used were a principal leadership questionnaire, a school climate questionnaire, and a teacher readiness questionnaire. The data collection technique used was distributing questionnaires to respondents who were classified as research samples. The questionnaire used was a closed questionnaire. To analyze the data, the researcher used analysis techniques by conducting a classical assumption test as a prerequisite test, then conducting simple linear regression analysis, and multiple linear regression. The results showed that principal leadership and school climate had a significant influence on teacher readiness in implementing the Independent Curriculum. The respective contributions were 25.2% (moderate) and 27.8% (weak), while the combined contribution of both reached 48.6% (moderate).